ACUTE ORAL TOXICITY STUDY OF ROOT METHANOL EXTRACT OF Goniothalamus lanceolatus Miq. AND ITS ISOLATED BIOACTIVE COMPOUND (PARVISTONE D) IN MURINE MODEL - MOHD ZOHDI, ROZAINI; MUHAMAD MUKHTAR, SHAHIDA; KAHARUDIN, FATIN AMELINA; ABDUL HAMID, KHURIAH; MOHD SIDEK, HASIDAH; RASOL, NURULFAZLINA EDAYAH; SRI WAHYUNI, FATMA; ISMAIL, NOR HADIANI (Malaysian Applied Biology, 2022)
Goniothalamus lanceolatus Miq. is widely used by the indigenous people of Sarawak, Malaysia as a folk remedy to treat various ailments including skin diseases, cold, and fever. A previous study reported that the root methanol extract, and parvistone D, an active compound of the plant, showed promising in vitro antiplasmodial activity against Plasmodium parasites. However, there is limited data reporting on its toxicological profile. Thus, this study aims to evaluate the potential toxicity of root methanol extract and parvistone D of G. lanceolatus in mice. The acute oral toxicity of the extract and compound was assessed at a single dose of 2000 and 500 mg/kg body weight, respectively. The animals were observed for any mortality, behavioral, motor-neuronal abnormalities, and body weight changes for 14 days. At the end of the experiment, relative organ weights were measured, and gross examination, as well as histopathological analysis, were performed. There was no sign of toxicity, and mortality seen in mice treated with G. lanceolatus root methanol extract, and parvistone D at the administered doses. In addition, no significant differences were observed in the body and relative organ weights between the control and treated groups. Gross and histopathological examinations showed normal appearance of the liver, spleen, kidneys, heart, and lungs as compared to their respective control groups. In conclusion, oral administration of root methanol extract, and parvistone D of G. lanceolatus are safe at the studied dosage levels and cause no acute toxicity in mice.